Desain Infrastructure as Code (IaC) untuk Automasi Pengamanan Jaringan: Hardening Router Berbasis Mikrotik - Haris, Arief Indriarto; Ferianda, Rd. Angga (Jurnal Pekommas, 2023)
The router plays an important role in managing data packet traffic in the network infrastructure, so its role is central and crucial. Disruption of Router functions by cyber-attacks will have a direct impact on the quality of Information Technology (IT) services in the network as a whole. Therefore, it is necessary to harden the router to protect it from cyber-attacks. But on the other side, securing (Hardening) Router also often encounters several obstacles and challenges, such as configuration errors or configuration processes that are repeated and tend to consume a lot of time and energy, especially if there are a lot of devices configured. By using the PPDIOO method, this study aims to design Infrastructure as Code (IaC) which focuses on MikroTik-based Router Hardening through an automation process. The results obtained were that all IaC designs had been successfully implemented through the automation process and no errors had been encountered. The total duration of hardening through automation was 4 minutes 28 seconds. The results of the system security test showed that the router was successfully protected and no vulnerabilities were encountered.